2021
DOI: 10.1111/psyp.13848
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory signals inhibit pupillary light reflex: Evidence from pupil oscillation

Abstract: Multisensory integration, which enhances stimulus saliency at the early stage of the processing hierarchy, has been recently shown to produce a larger pupil size than its unisensory constituents. Theoretically, any modulation on pupil size ought to be associated with the sympathetic and parasympathetic pathways that are sensitive to light. But it remains poorly understood how the pupillary light reflex is changed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Recent research has found that the interference of continuous flicker can reduce users' visual fatigue via peripheral vision (Zhao et al, 2021). This inhibition effect persisted when the visual flicker was task-irrelevant and out of attentional focus, but disappeared when the visual flicker was moved from the central field to the periphery (Yuan et al, 2021). Similarly, studies have shown that users' visual fatigue can be reduced by changing the frequency of dynamic flickers (Sato et al, 2021).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent research has found that the interference of continuous flicker can reduce users' visual fatigue via peripheral vision (Zhao et al, 2021). This inhibition effect persisted when the visual flicker was task-irrelevant and out of attentional focus, but disappeared when the visual flicker was moved from the central field to the periphery (Yuan et al, 2021). Similarly, studies have shown that users' visual fatigue can be reduced by changing the frequency of dynamic flickers (Sato et al, 2021).…”
Section: Introductionmentioning
confidence: 94%
“…, 2021). This inhibition effect persisted when the visual flicker was task-irrelevant and out of attentional focus, but disappeared when the visual flicker was moved from the central field to the periphery (Yuan et al. , 2021).…”
Section: Related Workmentioning
confidence: 99%
“…The present study was the first consecutive case comparison study designed to investigate the kinetic pupillary changes of eyes with HM. In our research, the fixation red light of the Pentacam system flickered at 3.0 Hz, which could induce measurable pupillary oscillations (Miller and Thompson, 1978;Naber et al, 2013;Yuan et al, 2021). Additionally, there was a timespan of 6-8 s for redlight fixation preparation before the scanning onset, which meant the switch on of the blue light illumination.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, it can be speculated that the Pentacam system could imitate the process of PLR. One of the major strengths of Pentacam is that it is a high-resolution system with a minimum resolution of 5 µm on Scheimpflug images, which is more accurate than known pupillometers (Bergamin and Kardon, 2002;Naber et al, 2013;Vartanian et al, 2015;Yuan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Gavriysky (1991) found that simply requiring a button press to light flashes prompted less initial constriction and increased the onset latency of the resulting light reflex, and inhibition of light reflex amplitude is also found when light probes are delivered during a difficult (subtract 7), compared to a simple (add 1), mental arithmetic task (Steinhauer et al, 2000). The response to flickering light is also inhibited during presentation of multisensory stimuli (Yuan et al, 2021). Using pharmacological agents to selectively inactivate the sphincter or dilator muscles, Steinhauer et al (2015) conclude that modulation of the light reflex during difficult cognitive processing is mediated by parasympathetic inhibition, which decreases sphincter constriction, increasing pupil diameter.…”
Section: Pupil Modulation In Psychophysiological Studiesmentioning
confidence: 99%